2014
DOI: 10.1186/s40536-014-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of problem solving competence: evidence from 41 countries that math and science education matters

Abstract: Background: On the basis of a 'problem solving as an educational outcome' point of view, we analyse the contribution of math and science competence to analytical problem-solving competence and link the acquisition of problem solving competence to the coherence between math and science education. We propose the concept of math-science coherence and explore whether society-, curriculum-, and school-related factors confound with its relation to problem solving. Methods: By using the PISA 2003 data set of 41 count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 49 publications
0
23
1
6
Order By: Relevance
“…Students are expected to be able to use mathematics and mathematical thinking, both in daily life learn and also learning science subjects (Saragih & Napitupulu, 2015). The results of the data analysis of PISA 2013 by Scherer & Beckmann (2014) stated that mathematical and scientific competencies significantly contribute to problem solving throughout the country. Phonapichat et al (2014) stated that the main purpose of teaching mathematics is to enable students to solve problems in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Students are expected to be able to use mathematics and mathematical thinking, both in daily life learn and also learning science subjects (Saragih & Napitupulu, 2015). The results of the data analysis of PISA 2013 by Scherer & Beckmann (2014) stated that mathematical and scientific competencies significantly contribute to problem solving throughout the country. Phonapichat et al (2014) stated that the main purpose of teaching mathematics is to enable students to solve problems in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu solusi yang ditawarkan untuk menyelesaikan masalah yang terjadi adalah dengan mengenalkan kepada siswa, sedini mungkin tentang pemecahan masalah matematika, memperkenalkan konsep matematika dalam bingkai pemecahan masalah (Scherer & Beckmann, 2014). Berdasarkan uraian permasalahan tersebut, maka penelitian ini bertujuan untuk mengetahui pengaruh pendekatan problem solving terhadap kemampuan representasi dan literasi matematis siswa SMP Kelas VIII.…”
Section: Pendahuluanunclassified
“…They found that the presence of absence of such guidelines in national frameworks was not significantly associated to PISA 2009 outcomes. Scherer & Beckmann (2014), instead, focused on mathematics, science and problem solving.…”
Section: The Relationship Between Curriculum and Performance In Intermentioning
confidence: 99%